AJ Popia / Jemima Azam Saiful Azam and Nur Atiqah Bakhtiar - Saiful Azam, Jemima Azam; Bakhtiar, Nur Atiqah (2022)
We are really grateful having this opportunity and chances to open the business of AJ Popia. Besides, we learn on how to communicate with people and giving them a great customer service. AJ Popia has become well know among our family and friends. We are really blessed having them as our customer and providing our first products business. All of our family and friends really supporting us by buying our products and follow us through Facebook page. AJ Popia starts by selling two types of crispy popia which is Popia Nestum and Popia Cheese. A lot of customer had bought our best-selling products which is Popia Nestum. Popia Nestum received many positive reviews by our family and friends. We using Facebook platform to promote and update our business and communicate with customers through WhatsApp. All of our customers are really happy and satisfied with our products.